Beyond discipline: the power of mentalization in reducing disruptive behavior in schools: a mixed-methods analysis of teacher–child interactions - Chelouche-Dwek, Gali; Clark, Carla; Fonagy, Peter (Frontiers in Psychology, 2025)
IntroductionEducators frequently encounter substantial challenges managing disruptive classroom behavior. This research examines Mentalization-Based Interventions (MBIs) within classroom to address disruptive behavior and emotional dysregulation, employing an attachment-focused perspective on teacher-student relationships. The study aimed to: (A) assess the effectiveness of MBIs in mitigating disruptive behavior and emotional dysregulation in classroom settings, and (B) analyze mentalizing patterns in teacher-student interactions during episodes of disruption.MethodsThe research observed 10 male pupils (X̄age = 8.4 years) across two alternative provision school classrooms in London, focusing on teacher-student interactions during disruptive incidents. In total, 142 incidents of disruptive incidents were documented. Teachers’ responses to pupil behavior were categorized and scored using six MBIs. Incidents were classified as resolved or unresolved based on the outcomes of these responses. Thematic analysis of incident transcripts was conducted and integrated with quantitative results through an embedded mixed-methods design.ResultsQuantitative findings indicated that MBIs predicted behavior resolution, with more interventions being associated with an increased likelihood of resolving disruptive incidents.DiscussionThe integration of qualitative analysis further underscored the efficacy of a multi-layered approach to addressing disruptive behavior. These findings contribute to the development of trauma-informed educational strategies and offer valuable insights for enhancing teacher-student interactions in settings where trauma and behavioral challenges are prevalent.Impact statementThis study demonstrates how Mentalization-Based Interventions (MBIs) can help teachers effectively manage disruptive classroom behavior, particularly among students with trauma histories. Through an analysis of real-world teacher-student interactions, the findings show that mentalizing interventions significantly increase the likelihood of resolving disruptive incidents. The study highlights the importance of teacher mentalization as a key tool for behavior management, offering practical insights for educators, caregivers, and mental health professionals working to foster emotionally supportive and trauma-informed learning environments.